PENGARUH IKLAN WEBSERIES PONDAN “CITA RASA RAISA” TERHADAP BRAND AWARENESS VIEWERS - Damanik, Shekina Hanna; Cristin, Pratiwi; Herwandito, Seto (Ilmu Komunikasi, FISIP Universitas Pasundan, 2024)
Advertising is part of the communication strategy to market the object or service presented by the company which is useful as a medium of reminder for consumers of the products advertised by the advertiser. Along with the growth of PONDAN, many emerging new premix flour so PONDAN still need to increase brand awareness. The author is interested to see the influence of advertising webseries PONDAN